2017
DOI: 10.1097/md.0000000000009191
|View full text |Cite
|
Sign up to set email alerts
|

Immediate relief of herniated lumbar disc-related sciatica by ankle acupuncture

Abstract: Background:Around 90% of sciatica cases are due to a herniated intervertebral disc in the lumbar region. Ankle acupuncture (AA) has been reported to be effective in the treatment of acute nonspecific low back pain. This study aims to evaluate the efficacy of a single session of ankle acupuncture for disc-related sciatica.Method:This will be a double-blinded, randomized controlled clinical trial. Patients diagnosed with disc-related sciatica will be randomly divided into 3 parallel groups. The treatment group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…We chose VAS because it is commonly used to measure pain intensity [12]. The same was applied by several studies conducted in the past [13,14]. An interventional study conducted by Singh et al, on 200 patients concluded that acupuncture provides effective relief from sciatica pain [13].…”
Section: Discussionmentioning
confidence: 99%
“…We chose VAS because it is commonly used to measure pain intensity [12]. The same was applied by several studies conducted in the past [13,14]. An interventional study conducted by Singh et al, on 200 patients concluded that acupuncture provides effective relief from sciatica pain [13].…”
Section: Discussionmentioning
confidence: 99%
“…In general, acupuncture ameliorates pain immediately and the effect lasts for a few hours. [ 33 , 34 ] However, assessments conducted immediately or soon after treatment may exaggerate the results. In addition, the influence which patients are accompanied with outcome assessors on objective effect assessment cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the incidence of lumbar intervertebral disc prolapse is increasing, and sciatica can happen in younger patients. [ 7 , 8 ] Suggesting that there are 5 out of every 1000 people suffering from sciatica in Western countries. In America, 25% of the medical insurance expenditure is paying for treating sciatica, and in England, the direct or indirect expenses for sciatica is £4.3 billion.…”
Section: Introductionmentioning
confidence: 99%